Kidney injury molecule 1 in the early detection of acute kidney injury—a systematic review and meta-analysis - Su, Yun; Yang, Xin; Cheng, Wei-Wei; Shang, Xue-Mei; Wang, Hong-Lian; Shen, Hong-Chun (Frontiers in Medicine, 2025)
BackgroundKidney Injury Molecule 1 (KIM-1) is a biomarker of proximal tubular injury that can be used for the early detection of acute kidney injury (AKI). This study was designed to systematically review the relevant literature to assess the role of urinary KIM-1 (uKIM-1) and blood KIM-1 (bKIM-1) in diagnosing adult AKI.MethodsWe searched PubMed, Embase, Cochrane, web of science for literature published until 7 August 2024, using the Quality Assessment Tool for Diagnostic Accuracy Studies (QUADAS-2). Sensitivity, specificity, and area under the curve (AUC) values from the included studies were combined using stata 18.ResultsIn total, 41 studies involving 1,790 patients were included. The estimated sensitivity of uKIM-1 for diagnosing adult AKI was 0.73 (95% CrI, 0.67–0.78), the specificity was 0.75 (95% CrI, 0.70–0.80), and the AUC was 0.81 (95% CrI 0.77–0.84); while the estimated sensitivity of bKIM-1 for diagnosing AKI was 0.72 (95% CrI 0.65–0.79), specificity was 0.79 (95% CrI, 0.70–0.86), and AUC was 0.81 (95% CrI 0.77–0.84).ConclusionuKIM-1 and bKIM-1 show potential as biomarkers for predicting AKI in adult patients, demonstrating relatively high sensitivity and specificity. However, the current meta-analysis does not provide sufficient evidence to make definitive conclusions, and further studies and clinical trials are needed to determine the practical utility of uKIM-1 and bKIM-1 in clinical diagnosis.